SUPPORTING THERAPY IN EOSINOPHILIC ESOPHAGITIS: WHY, WHOM, HOW? - N. V. KOROCHANSKAYA; S. N. SERIKOVA; M. A. BASENKO; S. S. SERIKOV (Кубанский научный медицинский вестник, 2018)
Aim. To demonstrate peculiarities of clinic features, difficulties of diagnostics and treatment of eosinophilic esophagitis using a clinic case.Materials and methods. The investigation of the clinic case in young woman with eosinophilic esophagitis is presented. The diagnosis was established 6 years after the manifestation of the disease on the stage of complications developed (esophageal stricture). A complex examination included endoscopy, morphologic methods and consultations with adjacent specialists (llergologist, ENT). Drug therapy was carried out by system and topical corticosteroids according to recommendations of Russian gastroenterological association from 2013.Results. The right diagnosis was established by the assessment of the clinic feature of dysphagia with revealing of mucosal eosinophilic infiltration during histological study of esophageal mucosal biopsies. The elimination diet and corticosteroid therapy improved the clinic course of the disease considerably. However, there were no signs of morphological changes of esophageal wall recovery. As a result, the patient needed to be treated and managed constantly. Based on the literature data the authors described variations of natural history of the disease, discussed the approaches to supporting therapy, and revealed group selection criteria of the patients most of all needed to anti-relapsing therapy.Conclusion. Eosinophilic esophagitis is a chronic immune-antigendependent inflammatory disease of the esophagus with insufficiently investigated etiopathogenesis. A number of questions concerning this disease need to be studied (clinical course, possibility of long-lasted remission and self-recovery, duration of corticosteroid therapy, etc).